Assessment of Learning Efficiency in Iraqi Nursing Education - Ahmed Sh. Alzuheri (Journal of Global Pharma Technology, 2018)
Many nurses make up the health system. Therefore, their education has a significant impact on the health of society. One way to ensure their abilities is to provide effective education. Nursing is professional discipline. A professional is an individual who possesses the knowledge and skill of experts in a particular field acquired through formal education in higher education institutions and through experience, which uses that knowledge and skill on behalf of the community through specific customer service 11. Objective: To assess the nursing education colleges regarding nursing education process. Design: Descriptive design (cross-sectional) survey study design has conducted throughout the period of 1 September 2016, to July 20th 2017 in order to Assessment of learning efficiency in Iraqi nursing education. After getting the approval of the University of Babylon / College of Nursing Council for the study, the researcher has submitted a detailed description including the problem statement, questionnaire and objectives of the study to the Ministry of Planning (Central Statistical Organization), which was accepted the study instrument. Later, the permission is presented at all nursing colleges in Iraq. Results: The finding of the study indicate that there is a clear shortage in the number of faculty members of all academic rank, in relation to the number of existing colleges, and also this shortage exists in the number of faculty members for students, in most colleges.Keyword:  Learning efficiency, Nursing education, Iraqi.